Acceptance of fingerprint identification ( e-jari) among supporting staff in UiTM Sri Iskandar, Perak / Ahmad Kidri Razali, Mohammad Norqamar Nazar and Muhamad Syamill Mokhtar - Razali, Ahmad Kidri; Nazar, Mohammad Norqamar; Mokhtar, Muhamad Syamill (2011)
Fingerprints are one of many biometric identification approaches being used nowadays to identify individual and verified their identity. This study is conducted to investigate the effectiveness of fingerprint identification among supporting staff in UiTM Perak. The methods being used by researchers are through interview, questionnaire and observation. The researchers made appointment and interview staff and office personnel in UiTM Perak to obtain information regarding the fingerprint identification. Besides that, the researchers also distributed among the supporting staff and make an observation. Fingerprint identification is selected among other biometric device because it is cheaper compared to others. Besides that, human fingerprints are unique. Reliability of fingerprint identification device also contributes to the selection of fingerprint identification. By using fingerprint identification, it can provide higher security level, eliminate buddy clocking, increase productivity and simplify many aspects of work, improve punctuality, and eliminate cards thus there will be no recurrence cost. The researchers found that fingerprint identification give numerous benefits to the organization in order to achieve the organization goal. The researchers recommended that fingerprint identification should be applied among student ofUiTM Perak.